1972
DOI: 10.1007/bf01976433
|View full text |Cite
|
Sign up to set email alerts
|

Light and electron microscopy of pea streak virus in crude sap and tissues of pea (Pisum sativum)

Abstract: In epidermal strips of pea plants with the Wisconsin strain of the pea streak virus, studied from about three weeks after inoculation, extensive parts of the cytoplasm stained red when treated with phloxine and methylene blue. Usually the stained areas were not sharply delimited. Sometimes more or less well-defined granular and often vacuolated inclusion bodies were observed. They were mainly located near the nucleus and along the cell wall.When sap of such plants was studied in the electron microscope, either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Our results show that RCVMV has an intracellular distribution comparable to that of other members of the carlavirus group studied so far: potato virus M (Tu and Hiruki, 1970), potato virus S (de Bokx and Waterreus, 1971), P a s s i f t o r a latent virus (Bos and Rubio-Huertos, 1971), carnation latent virus (Castro et al, 1971), pea streak virus (Bos and Rubio-Huertos, 1972), and the recently reported cole latent virus (Kitajima et al, 1970) apparently also belonging to the group. With none of these viruses has true crystallization been observed, perhaps because their particles are not sufficiently straight although rather rigid.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Our results show that RCVMV has an intracellular distribution comparable to that of other members of the carlavirus group studied so far: potato virus M (Tu and Hiruki, 1970), potato virus S (de Bokx and Waterreus, 1971), P a s s i f t o r a latent virus (Bos and Rubio-Huertos, 1971), carnation latent virus (Castro et al, 1971), pea streak virus (Bos and Rubio-Huertos, 1972), and the recently reported cole latent virus (Kitajima et al, 1970) apparently also belonging to the group. With none of these viruses has true crystallization been observed, perhaps because their particles are not sufficiently straight although rather rigid.…”
Section: Discussionsupporting
confidence: 67%
“…Sander's inclusions may resemble the inclusions we observed with pea streak virus (Bos and Rubio-Huertos, 1972). The amorphous inclusions found by Rubio-Huertos (1964) together with crystals in peas contained pinwheel structures and presumably were caused by a contaminating virus, possibly bean yellow mosaic virus.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Virus particles occurring in large quantities with their ends attached to membrane remnants have earlier been reported and depicted by Bos and Rubio-Huertos (1972) for pea streak virus and by for a pea latent strain of red clover vein-mosaic virus. Such complexes have also been described for a carlavirus in shallot by Cadilhac et al (1976).…”
Section: Fig 5 E•ektr•nenf•t• Van Gezuiverdpreparaat Van Het Latentmentioning
confidence: 97%
“…Our failure to detect 'pinwheel' inclusions in PopMV-inlected plants indicates that it is not a member o f the Potyvirus group and, moreover, unlikely to be transmitted by mites, fungi or whiteflies. Conversely, the common occurrence of PopMV particles looselyassociated in aggregates is characteristic o f authentic members of the Carlavirus group such as Passiflora latent [12], pea streak [13] [17] viruses. The absence from infected plants of intracellular 'pinwheel' inclusions but occur rence of filamentous particles within ovoid particle aggregates thus provides indirect but additional evidence for the inclusion of PopMV in the Carlavirus group, and indicates that aphids are probably responsible for its slow natural spread [3], Although Chaitophorus pcpulicola was associated with the spread of PopMV in Canada [3], the virus was transmitted by none of six other aphid species (Aphis craccivora, Aphis fahae, Chaitophorus versicolor, Macrosiphum euphorbiae, Myzus persicae and Pterocomma populeum) tested in Europe [1,9].…”
Section: Discussionmentioning
confidence: 99%